Myenteric Denervation of the Gut with Benzalkonium Chloride: A Review of Forty Years of an Experimental Model - Sérgio Britto Garcia; Stefânia Bovo Minto; Isabela de Souza Marques; Vinicius Kannen (Canadian Journal of Gastroenterology and Hepatology)
Experimental denervation of organs plays a key role in understanding the functional aspects of the normal innervation as well as the diseases related to them. In 1978 the experimental model of myenteric denervation of the rat gut by serosal application of benzalkonium chloride (BAC) was proposed. BAC is a positively charged surface-active alkylamine and is a powerful cationic detergent, which destroys bacteria after ionic attraction and for this reason is largely used as a surgical antiseptic. Since its initial report, the BAC-induced myenteric denervation model has been used to study many functional and pathological aspects of the enteric nervous system. So far this is the only pure method of myenteric denervation available for research in this area. Promising reports in the literature have shed light on the possibilities for the development of new uses of the BAC-denervation experimental model as a therapeutic tool in some pathological situations. This review aims to shed light on the main historical and recent findings provided by this experimental model.